Reclaiming the Food System: Agroecological Pedagogy and the IALA María Cano (Alternautas, 2022)
Industrial agriculture has been one of the key contributors to global warming and consequent climate disasters worldwide. In 2014, 44-57% of global greenhouse gas emissions were produced by industrial food production; principally from deforestation, transportation of products, their processing and refrigeration (GRAIN, 2014). This paper will focus on the case of the Instituto Agroecologico Latinoamericano (IALA) María Cano in Colombia, which aims to use knowledge as resistance in an epistemo-political struggle against industrialised agriculture. The piece will theoretically outline the phenomenon of industrial agriculture, the impact this has on societies and ecologies, as well as the overarching epistemologies that maintain this.